2016
DOI: 10.1039/c6tb02025a
|View full text |Cite
|
Sign up to set email alerts
|

Drug delivery and controlled release from biocompatible metal–organic frameworks using mechanical amorphization

Abstract: We have used a family of Zr-based metal–organic frameworks (MOFs) with different functionalized (bromo, nitro and amino) and extended linkers for drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(139 citation statements)
references
References 60 publications
4
135
0
Order By: Relevance
“…Previously, we and others have shown that UiO‐66 is biocompatible, while the cytotoxicity of DCA ‐loaded MOFs is dependent on surface chemistry, and incorporation of a second drug can dramatically enhance overall cytotoxicity . As well as DCA , we have chosen α‐cyano‐4‐hydroxycinnamic acid ( α‐CHC ), a molecule recently proposed as an anticancer agent, due to the relatively low p K a of its carboxylate unit (2.2), comparable with the one of DCA (1.4).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we and others have shown that UiO‐66 is biocompatible, while the cytotoxicity of DCA ‐loaded MOFs is dependent on surface chemistry, and incorporation of a second drug can dramatically enhance overall cytotoxicity . As well as DCA , we have chosen α‐cyano‐4‐hydroxycinnamic acid ( α‐CHC ), a molecule recently proposed as an anticancer agent, due to the relatively low p K a of its carboxylate unit (2.2), comparable with the one of DCA (1.4).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, The MOF structures have been loaded with fluorescent molecules (e.g., calcein), and demonstrated the use of mechanical amorphisation processes for the controlled delivery of the guest molecules (Figure 15). The research results showed that the fine balance between the material's pores and the guest molecules is crucial for achieving effective release of the guest molecules [87]. …”
Section: Drug Delivery Systems (Dds)mentioning
confidence: 99%
“…Second, MOFs are intrinsically biodegradable as a result of relatively labile metal–ligand bonds, making it possible to rapidly degrade and clear the nanocarriers after the intended task is completed (Rocca, Liu, & Lin, ). Though the moderately low chemical and aqueous stability of MOFs has limited their scope for industrial applications, this drawback of MOFs is considered an advantage for delivery system in light industry or medicine applications, as the MOF particles can be biodegraded and eliminated from the body after the compounds are released (Orellana‐Tavra et al, ). At present, there are some studies of MOFs used as nanocarriers for drug delivery (ibuprofen [Erucar & Keskin, ], alendronate [Golmohamadpour, Bahramian, Shafiee, & Mamani, ], doxorubicin hydrochloride [Bhattacharjee et al, ]), VOC removal (Xu et al, ; Zhang, Lv, Shi, Yang, & Yang, ; Zhu, Hu, Tong, Zhao, & Zhao, ), and sustained release of small molecule dyes (Li et al, ) and cosmetic molecules (caffeine and urea; Erucar & Keskin, ).…”
Section: Introductionmentioning
confidence: 99%
“…One well‐recognized challenge of MOFs is their poor aqueous stability, limiting their scope for practical applications. However, this drawback of MOFs is considered an advantage for delivery system in food industry or biomedicine applications, as the MOF particles can be biodegraded and eliminated from the body after the volatile compounds are released (Orellana‐Tavra et al, ).…”
Section: Introductionmentioning
confidence: 99%